2021
DOI: 10.1007/s40858-020-00417-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of physiological races of Exserohilum turcicum isolates from maize in Argentina and Brazil

Abstract: Northern corn leaf blight (NCLB) is one of the most important diseases in maize worldwide. It is caused by the fungus Exserohilum turcicum, which exhibits a high genetic variability for virulence, and hence physiological races have been reported. Disease control is based mainly on fungicide application and host resistance. Qualitative resistance has been widely used to control NCLB through the deployment of Ht genes. Known pathogen races are designated according to their virulence to the corresponding Ht gene.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The details of the districts surveyed and the areas from which diseased isolates were collected for variability studies are given in Table 1 . Field samples were labeled, kept in cold boxes, and brought to the laboratory for further study [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of the districts surveyed and the areas from which diseased isolates were collected for variability studies are given in Table 1 . Field samples were labeled, kept in cold boxes, and brought to the laboratory for further study [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Colonies were observed at 2–3 day intervals until full growth was attained. Small portions of fungal mycelium from fully grown culture were aseptically transferred to plates of fresh PDA culture medium in order to obtain pure cultures of E. turcicum [ 16 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The physiological race of S. turcica present in the Indian subcontinent has been determined to be Race 2 [98]. Studies have also shown that S. turcica migration is likely over long distances, which could shift virulence to new regions [99]. Selection pressure, sexual recombination within the pathogen, and the capability to migrate long distances may create more virulent populations and contribute to spatial and temporal race population shifts.…”
Section: Variability and Population Structure Of E Turcicummentioning
confidence: 99%
“…Leonard & Suggs is the causal pathogen of the highly lethal and devastating foliar disease northern corn leaf blight (NCLB), which occurs in all maize-producing regions ranging from tropical to temperate zones, seriously threatening the maize production with significant losses in both quality and quantity. 1,2 This fungus usually produces a large number of melanins in hyphae and its colony on culture medium shows dark to black-gray color. In addition to hyphae, its conidia are highly melanized and olivaceous brown to dark gray, which is associated with ellipse-or cigar-shaped gray-to tan-colored lesions on the corn leaves.…”
Section: Introductionmentioning
confidence: 99%